Perbedaan perilaku agresi antara siswa laki-laki dan siswa perempuan di SMPN 1 Kasreman Ngawi - Arih Merdekasari; Moh Toriqul Chaer (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2017)
This study aims to examine differences in aggressive behavior among male students and female students at the Junior High School 1 Kasreman. The method of research is a scientific activity carried out in stages to achieve research objectives. The research used is descriptive survey research. The study population is students aged 12-15 years (early adolescent phase) at the Junior High School 1 Kasreman. The sampling technique used purposive random sampling technique. Characteristics of the study sample are students aged 12-15 years in junior high school 1 Kasreman as many as 104 students. A statistical significance level of the test uses the hypothesis test in both directions. Hypothesis test shows the value of aggressive behavior (sig = 0.018), it can be seen that the p-value of <0.05, so it can be concluded that hypothesis was accepted. There are differences in the level of aggressive behavior among girls and boys.